Pemanfaatan waktu luang asrama putra untuk mengaji di pondok pesantren darul kamal - Jayadi, Iqbal (At-Tadbir: Jurnal Manajemen Pendidikan Islam, 2022)
It is not surprising that the Arab community adorns the speed of time with the flash of a sword, al-waqt Ka al-saif fa in lam taqtha "hau gatha' aka (time is like a sword if you don't use it, it will cut you)." Meanwhile, quoting from a personal devotional book in the summary of 5000 Pearls that we must be vigilant and careful about the rotating wheel of time because if we are complacent it will be crushed. By seeing how important the value of time is and how great God's grace is hidden in it. The Qur'an pays great attention to the problem of time seen from various angles and various forms of personification. Allah swears at the beginning of certain chapters in the Qur'an by using certain phases of time such as wal laili wan nahari (by the night and day), wal fajr (by the time of dawn), wad dhuha (by the time of Duha), and walashr (by the time of dawn). asr time).